Sustainable Entrepreneurship in Indonesia with Leveraging Green Practices for Business Success - Yusuf Iskandar; Kurniawan; Andri Ardhiyansyah; Froilan Delute Mobo (Vifada Management and Social Sciences, 2026)
Purpose: This study looks into how government policies, technical innovation, green entrepreneurship promotion, environmental awareness, and green business growth affect the expansion of green businesses and the mitigation of environmental impacts through social entrepreneurship in Indonesia. Research Design and Methodology: A quantitative analysis was carried out on a sample of 296 respondents using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) route analysis. The data was analyzed using model fit indices, hypothesis testing, measurement model analysis, and descriptive statistics. Findings and Discussion: The findings show a strong positive correlation between government policy, social entrepreneurship, technological innovation, environmental impact reduction, green business growth, and environmental awareness as well as green entrepreneurship promotion. The results highlight how crucial it is to promote green entrepreneurship, technological innovation, and social entrepreneurship in Indonesia in addition to encouraging environmental awareness and enacting regulations that support these sectors. Implications: This research implies the importance of strengthening policies, providing support for business actors, and fostering collaboration among stakeholders to accelerate the development of sustainability and green entrepreneurship in Indonesia.